Improving Antimicrobial Properties of Biopolymer-Based Films in Food Packaging: Key Factors and Their Impact - Wardejn, Sonia; Wacławek, Stanisław; Dudek, Gabriela (International journal of molecular sciences, 2024)
Biodegradable films derived from polysaccharides are increasingly considered eco-friendly alternatives to synthetic packaging in the food industry. The study's purpose was to improve the antimicrobial properties of biopolymer-based films made from starch, chitosan, alginate, and their blends (starch/chitosan and starch/alginate) and to evaluate the effects of modifiers, i.e., plant extracts, plasticizers, cross-linking agents, and nanofillers. Films were prepared via the Solution Casting Method and modified with various plasticizers, calcium chloride, oxidized sucrose, and nanofiber cellulose (NC). Chestnut, nettle, grape, and graviola extracts were tested for antimicrobial activity against Staphylococcus epidermidis, Escherichia coli, and Candida albicans. The film's mechanical and hydrophilic properties were studied as well. The chestnut extract showed the strongest antimicrobial properties, leading to its incorporation in all the films. The chitosan films displayed better antibacterial activity against Gram-positive than Gram-negative bacteria but were ineffective against C. albicans. NC significantly improved the mechanical and antimicrobial properties of the chitosan films. The alginate films, modified with various plasticizers cross-linked with calcium chloride, demonstrated the highest antimicrobial efficacy against E. coli. The starch films, cross-linked with oxidized sucrose, exhibited slightly lower antimicrobial resistance due to a more compact structure. Films such as ALG6 and ALG5, including plasticizers EPGOS and PGOS, respectively, indicated optimal hydrophilicity and mechanical properties and achieved the best antimicrobial performance against all the investigated microorganisms. All these findings highlight the potential of these biodegradable films for food packaging, offering enhanced antimicrobial activity that prolongs shelf life and reduces spoilage, making them promising candidates for sustainable food preservation.
Keywords: Microbial Sensitivity Tests; obaly potravin; food packaging; environmentally friendly; algináty; změkčovadla; chitosan; Plasticizers; Starch; Escherichia coli; biofilms; škrob; antimicrobial; mikrobiální testy citlivosti; rostlinné extrakty; antiinfekční látky; Anti-Infective Agents; Plant Extracts; biopolymery; Biopolymers; Staphylococcus epidermidis; Alginates; Candida albicans; Chitosan; Food Packaging